The Shari'ah Court Procedure In Mindanao - Philippines: An Understanding - Alioden, Saada Samad; , Prof. Dr. Suparman Syukur, M.A (2014)
In this study, the researcher seeks to understand and to describe the Shari'ah Courts procedure in Mindanao - Philippines. Especially, this study find the answer to the following questions, namely: firstly, what is the origin of Shari'ah Courts in Mindanao - Philippines?; Secondly, what are the Shari'ah Courts in Mindanao - Philippines?; Thirdly, what are the basic jurisdictions of the Shari'ah Courts in Mindanao - Philippines? And Finally, what are the Special Rules of Procedure governing the Shari'ah courts in Mindanao - Philippines? The main objective of this study is to cater the need of Shari'a Students and prospective candidates to the Special Shari'a Bar Examinations in the Philippines. This research uses of Descriptive and Qualitative research method. This study is also a kind of library research where the research data and information obtained from major books which are related to this research. This study was conducted at Sultan kudarat, Cotabato City, where the researcher resides on second semester of academic year 2014 - 2015. However, since the researcher was studying at MUHAMMADIYAH UNIVERSITY OF SURAKARTA, Indonesia, It was presented and defended to the said university on September 17, 2014. In the case of this study, descriptive and qualitative research approach in gathering, evaluating and handling data was utilized. Through applying descriptive and / or qualitative methods can ensure reliability in the research. In this research, an inductive approach was used. It is an approach that searches for a specific data related to this research from a variety of data sources in order to acquire essential knowledge and information. To assess the validity of the instruments used in this research such as review of related literature and review of related studies content validity was established where a recognised experts in the area of study (Thesis adviser, Thesis proposal professors, and other qualified persons) was asked to give their opinion on the validity of the tool. To answer the problems mentioned above in this study scientifically, hence the researcher uses in - depth reading and fact - finding on the following data sources: first, the data sources from a binding law such as P.D. 1083 otherwise known as the Code of Muslim Personal laws of the Philippines, from the Special Rules of Court Procedure governing Shari'a Courts in Mindanao - Philippines and from the Rules of Court in the Philippines;Second, the data sources as a results of study through many literatures, books, magazines, journals, newspapers, and thesis. Third, the data sources explanations from primary and secondary materials such as encyclopedia and dictionary. The qualitative data taken from the data sources will be analysed through a logical analysis. Finally, the information from the document review could also give clarity to the research questions. From the data analysis result, the establishment of the Shari'a Courts in the Philippines has been originally conceived in the 1976 Tripoli Agreement entered into by and between the Philippine Government and the Moro National Liberation Front under the auspices of the Organization of Islamic Conference. It has been agreed, among other things, that in the areas of autonomy, the Muslims shall have the right to set up their own Courts which implement the Islamic Sharia'h Laws. In addition, there are three levels of Shari'a Courts in the Philippines, namely: Shari'a Appellate Court, Shari'a District Court and Shari'a Circuit Court. Moreover, The Shari'a courts of the Philippines are courts of limited and special jurisdiction because their jurisdiction is confined to the class of cases enumerated by PD 1083 otherwise known as the "Code of Muslim Personal Laws." They do not exercise the power conferred upon a court of general jurisdiction, i.e., Regional Trial Court, which has the power to take cognizance over all cases not falling under the exclusive original jurisdiction of any court, tribunal, board or officer. Furthermore, the Special Rules of Procedure Governing the Shari'a Courts were promulgated by the Supreme Court pursuant to Articles 148 and 158 of the Code of Muslim Personal Laws. These special rules of procedures take effect immediately, Approved unanimously on September 20, 1983.